The Contribution of Microlending Models to the growth of Micro and Small Entrepreneurs - Goodluck Goda; William Clifford Gomera (Journal of Business and Management Review, 2022)
Microfinance has been providing microcredit services to beneficiaries through group, individual, association loans, community banking, and corporative microlending models. The sector has been fostering the growth of business in the economy by enabling entrepreneurs to participate in a variety of income-generating activities. However, there is limited information on the extent the microlending models contribute to the performance of micro and small enterprises. Therefore, the current research primarily intended to assess the contribution of Microfinance Bank's microlending models to the growth of micro and small entrepreneurs in Tanzania. This was a mixed approach study which adopted explanatory design and used convenience and purposive sampling techniques to obtain 179 respondents. Questionnaires, document review and interviews were used to collect both primary and secondary data. Statistical Packages for Social Science were used to quantitatively analyse field data using descriptive statistics (SPSS). MAXQDA10 was also used to conduct a content analysis of qualitative data. The findings of the study show that microlending models of microfinance banks contribute to the growth of micro and small entrepreneurs. It is thus recommended that microfinance banks should use appropriate lending model that is compatible with the nature of micro and small firms for growth and sustainable operations as they constitute the larger portion of lending clientele.